De novo hepatocellular carcinoma post‐multivisceral transplantation in a child. (27th July 2017) - Tran, P.; Zhou, S.; Wang, L.; Finegold, M.; Mascarenas, L.; Alexopolous, S.; Genyk, Y.; Kerkar, N.
Abstract: De novo hepatocellular carcinoma (HCC) post‐transplantation in patients without viral hepatitis is extremely rare, with only three reported adult cases in the English literature. Here, we present a case of de novo HCC that developed in a 7‐year‐old female, who at 8 months of age received a liver, small bowel, spleen, and pancreas transplantation 6.5 years ago for gastroschisis and total parenteral nutrition (TPN)‐related cirrhosis. The post‐transplant course was complicated by Epstein‐Barr virus (EBV) infection, post‐transplant lymphoproliferative disease, and subsequent development of multifocal EBV‐associated post‐transplant smooth muscle tumors (EBV‐PTSMT) in the small bowel 1 year and 10 months after transplantation, respectively. This was managed by reducing immunosuppression with rituximab and EBV‐specific cytotoxic T‐cell therapy. She was noted to have a new lesion in her transplanted liver graft 6.5 years post‐transplantation that was diagnosed as HCC. The HCC was resected, and the patient remained clinically stable for 7 months. At that time, recurrence of the HCC was discovered on MRI. She passed away 6 months after. To the best of our knowledge, this is the first reported occurrence of de novo HCC post‐transplantation in the pediatric population that is unrelated to viral hepatitis in either recipient or donor.